2016
DOI: 10.3832/ifor1505-008
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, carbon and energy evaluation of Eucalyptus nitens short rotation bioenergy plantations in northwestern Spain

Abstract: This study provides essential information related to the nutrient and carbon levels and the energy potential of Eucalytpus nitens (Deane & Maiden) Maiden bionenergy plantations located in northwestern Spain. Nutritional analysis showed that leaves and bark had the highest concentrations of N, P, K and Mg. Carbon concentration was constant for all above-ground tree components. Nutrients and carbon were analyzed at stand level according to plantation productivity. Stemwood, the main tree component at the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
3
7
1
Order By: Relevance
“…The contribution of branches to total tree biomass continued to increase, although not at the same speed as that of the stem. These results agreed with those reported by González-García et al (2016b), who noted that increased tree growth or increased biomass production with age led to an asymptotic decline in the contribution of the foliage and fine and medium roots to the total biomass, whereas the contribution of timber, branches, and thick roots increased significantly.…”
Section: Discussionsupporting
confidence: 82%
“…The contribution of branches to total tree biomass continued to increase, although not at the same speed as that of the stem. These results agreed with those reported by González-García et al (2016b), who noted that increased tree growth or increased biomass production with age led to an asymptotic decline in the contribution of the foliage and fine and medium roots to the total biomass, whereas the contribution of timber, branches, and thick roots increased significantly.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, considering the mean values per tree, the highest ash contents corresponded to the willow and poplar clones, with values between 1.17 and 2.18%, whereas for both pine and chestnut the values were below 1%. These values are similar to those reported by other authors for productive species, e.g., Kumar et al [19] reported values of between 0.43 and 1.09% for the wood fraction in Eucalyptus hybrids, and González García et al [43] reported a value of 0.76% for the same fraction in Eucalyptus nitens. Therefore, the high ash content in crown and bark fractions reduces their fuel quality in comparison with the wood fraction.…”
Section: Proximate Analysissupporting
confidence: 90%
“…In Pérez (1995), P concentrations in L. apiculata leaves were very similar to those of the present study (mean 0.11%). Regarding E. nitens, the N, P, and K foliage concentrations were lower than those reported by González-García et al (2015) and Bonomelli and Suárez (1999). In contrast, the nutrient concentrations in P. radiata are in the range reported in the literature (Zas and Serrada 2003;Hawkins et al 2010).…”
Section: Nutrient Content In Plant Organscontrasting
confidence: 67%